The Women's Entrepreneurial Ecosystem in Tunisia: How Can Entrepreneurial Skills Overcome Obstacles? - Amin, Bardaa Mohamed (Indonesian Journal of Business and Entrepreneurship, 2024)
Background: Over the last decade, the definition of 'entrepreneurial ecosystems' has acquired great importance in research processes related to the management and business field. In this sense, the term has been used in numerous documents of diverse nature to describe the interaction of political, social, economic, cultural, and environmental aspects that enable the development of entrepreneurial activity in a given region. Female entrepreneurship represents untapped economic potential and assets in Tunisia. Nevertheless, women are likely to be disadvantaged in their entrepreneurial journey due to many difficulties they face that have been exacerbated by and even before the COVID-19 crisis. To unlock the value that women can bring to the economy, society, themselves, and their families, it is necessary to cultivate an entrepreneurial ecosystem that encourages and supports female entrepreneurship in general. Purpose: This research article examines how entrepreneurial skills represent significant resources for overcoming the barriers inherent in women's entrepreneurial ecosystem. Design/methodology/approach: In addition, it tests the mediating effects of emotional intelligence and their impact on the relationship.Findings/Result: Focusing on a population of 60 young women entrepreneurs in Tunisia, the results of our study show that entrepreneurial skills play a primordial role in women entrepreneurs overcoming ecosystem barriers. Conclusion: The outcomes of this research indicate that entrepreneurial skills are essential for women to succeed in the entrepreneurial ecosystem. Furthermore, the study suggests that emotional intelligence has a beneficial impact.Originality/value (State of the art): The added value of this research is that it explores how entrepreneurial skills influence the obstacles within the entrepreneurial ecosystem, with emotional intelligence playing a mediating role. Keywords: entrepreneurial ecosystem, women entrepreneurs, entrepreneurial skills, obstacles, emotional intelligence